التدريبات اللغوية في كتاب دروس اللغة العربية (دراسة وصفية تحليلية): Linguistic Exercises in Durūs Al-Lughah Al-‘Arabiyyah: a Descriptive and Analytical Study - Ronny Mahmuddin (البصيرة: مجلة الدراسات الإسلامية, 2025)
This study aims to describe and analyze the linguistic exercises employed in the teaching of applied Arabic as presented in Durūs al-Lughah li Ghair al-Nāṭiqīna bihā, Volume I. The research adopts a qualitative descriptive design using a library-based approach through content analysis of the textbook. The findings reveal that the linguistic exercises in the teaching of applied Arabic in this textbook demonstrate pedagogical excellence through the systematic presentation of three types of varied language drills, all conducted in fuṣḥā (standard Arabic) without translation. These include: (1) pattern drills, which train learners to internalize language use through continuous and repetitive practice with diverse exercise models; (2) semi-pattern drills, which develop learners’ ability to comprehend sentences and apply them effectively in both spoken and written expression; and (3) communicative drills, which cultivate learners’ communicative competence in both monologic and dialogic contexts.